Complex Environment Calls for Complex Thinking: About Knowledge Sharing Culture - Block, Madeleine (Journal of Reviews on Global Economics, 2019)
The purpose of this research is to enhance understanding of how organisations can master global disruptions and take advantage of them. A conceptual paper is presented. For the purpose of analysing organisation-environment-relations, the theoretical umbrella adopted here is the system theory. Also, the study has mainly incorporated concepts of innovation and knowledge sharing as well as theory of organisational culture. This research reflects the zeitgeist for at least two reasons. Firstly, in current times of global disruptions, the need for innovation and the process of knowledge sharing have both become central topics for organisations. Secondly, global disruptions make us aware of being challenged, traditional one-sided thinking does not work any longer in such an increasingly complex world. The alternative is to think in terms of relations and holistically, while accepting the existence of instability. Moreover, this study has made several contributions to research and implications for practice. First of all, this article adds value for the fields of research of organisational management, innovation management and organisational culture. Secondly, major contributions of this research are the developed intra-organisational learning loop as a guiding framework for how to handle disruptions, and furthermore, the system and disruption model. This latter model is developed with the aim of identifying types of organisational culture which are determined by the intensity of disruptions and the type of organisational system. Thirdly, the organisational culture of knowledge sharing is more specified in greater detail, with the intention of fostering innovative behaviour. Lastly, this study contributes mainly to the theory of social systems by explaining the organisation-environment relations, proposing to strengthen the organisation internally, for example, through culture and being open towards external changes. Characteristics of organisations have been worked out and key features of effective organisations for the future are proposed. This study is not free of limitations, which offer opportunities for future research. Firstly, it is a conceptual paper and the results have not yet been empirically proven. So, an interesting possibility for further research could be to test the proposed models and framework empirically. Secondly, the scope of this study is broad and thus it was not feasible to analyse each component of the model in detail. Future studies could further investigate the proposed models in more detail and explore more precisely out how to use it, for example, by developing a practical guideline for managers. Another useful avenue of future research could be an in-depth study of organisations, comparing them based on the suggested features of effective and restrictive organisations and results, which would potentially enable deeper classifications of organisations.